Contribution of forensic autopsy to scene reconstruction in mass fire casualties: A case of alleged arson on a floor consisting of small compartments in a building. Issue 1 (January 2015) - Michiue, Tomomi; Ishikawa, Takaki; Oritani, Shigeki; Maeda, Hitoshi
Highlights We report the forensic autopsy findings of 16 fire victims in an alleged arson case. Full autopsy, following toxicological and biochemical analyses, contributed to scene reconstruction. Forensic case study of fire casualties is important for disaster prevention.